METODE MENGEMBANGKAN SPIRITUAL QUOTIENT (KECERDASAN SPIRITUAL) ANAK USIA DINI - Idris Afandi (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2023)
Spiritual Quotient is one type of intelligence that is increasingly recognized the importance of the formation of children's character. Spiritual intelligence is related to the ability to develop relationships with yourself, others, and God or greater power. In the context of early childhood education, it is important to develop spiritual intelligence because at this age the child is developing self -concept, emotions, and morals that will shape the foundation of their personality in the future. In this article, methods will be discussed that can be used to develop the spiritual intelligence of early childhood. This article will explain the definition of spiritual intelligence and why it is important to develop it in early childhood. In addition, this article will also discuss effective methods for developing spiritual intelligence in early childhood, including examples of activities that can be done at home or at school. These methods can include introducing children to spiritual values, facilitating the practice of meditation or reflection, providing experiences that stimulate a sense of connection with nature or other living things, and so forth.